Decreasing Microbial Fuel Cell Start-Up Time Using Multi-Walled Carbon Nanotubes - Antonia Jimenez Rodríguez; Antonio Serrano; Teresa Benjumea; Rafael Borja; M. El Kaoutit; Fernando G Fermoso (Ital Publication, 2019)
The bioelectrochemical systems are a sustainable technology that can be used to obtain electricity and/or reduced compounds. However, this novel technology presents several challenges prior to its implementation at full-scale. The aim of the present study was to evaluate different nanomaterials of electrode and mediators to increase the performance of BioElectrochemical Systems production. In order to achieve this objective, it was compared the use of Multiwall Carbon Nanotubes and Multiwall Carbon Nanotubes plus electron exogenous mediator (Meldola’s Blue) against plain graphite anode in order to evaluate the overall start-up time and other electro-chemical features. The use of multi-walled carbon nanotubes reduces substantially (by 75%) the start-up time required in a microbial fuel cell to produce stable voltage both, with and without the use of mediator compare to the plain anode. This reduction of the required time can be a consequence of the formation of anodic binders between this compound and the bacteria. With the independence of the start-up time, the current production was similar in the three studied cases, about 650 mV. Use of nanotubes modified anode surfaces might be especially interesting in cases of recovery after unstable operation of a microbial fuel cell, and/or reducing the start-up time for the generation of energy from new systems.